Pengaruh Penggunaan Laba Dan Arus Kas Untuk Memprediksi Kondisi Financial Distress - Rachmat Ramadhani; Erna Nur Ifah; Dany Prio Hutomo (BADAN PENERBIT STIEPARI PRESS, 2022)
This study aims to examine the effect of earnings and cash flow in predicting financial distress conditions in manufacturing companies listed on the Indonesia Stock Exchange. This study uses a quantitative descriptive analysis model. Data obtained from secondary data, namely data obtained from other parties in the form of published reports for the period 2020-2021. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange. The number of samples in this study were 80 companies. The sampling method used is purposive sampling. The data is processed using SPSS. Based on the conclusion of the analysis results, it is known that profit has no effect on financial distress because the profit variable has a sig value of 0.973 this value is greater than the alpha significant value (0.05) and cash flow has an effect on financial distress conditions, where the obtained significance figures are 0.000 and 0.001 more. smaller than 0.05, which means that cash flow has a significant effect on predicting financial distress.